Flipped classroom in higher education: A bibliometric analysis and proposal of a framework for its implementation - Limaymanta, Cesar H. (2021)
The flipped classroom as an educational model is perfectly aligned with the current demands of higher education. Therefore, the objectives of this article were to carry out a bibliometric analysis of the scientific production of the flipped classroom in higher education (2012-2020) and to propose a framework for its implementation in face-to-face, blended or online learning modalities. The records were recovered from the Web of Science Core Collection and Scopus, from which, after a five-phase methodological process, a consolidated dataset of 782 documents was obtained. The results showed the importance of the subject matter as scientific production reflected a continuous growth during the period of study. For their part, the most productive authors come from various institutions worldwide with an H index of over 50. The collaboration indicators show the growth trend of these indexes over the years, which reflects the capacity to generate national and international impact in the documents published in collaboration. The keywords co-occurrence analysis showed that the flipped classroom as a technological and innovative approach is complemented by active learning, blended learning, e-learning, ICT, teaching method, among others. Finally, a framework with five components was proposed as a basic guide for the implementation of the flipped classroom in higher education.